Deficiency of protein C inhibitor in combined factor V/VIII deficiency disease. - Marlar, R A (1980)
Activated protein C is an anticoagulant plasma protease enzyme that inactivates Factors V and VIII in plasma. Normal plasma contains a protein that inhibits activated protein C and that is distinct from previously described plasma protease inhibitors. Protein C inhibitory activity is not detectable in plasmas from four unrelated patients with combined Factor V/VIII deficiency but is present in normal amounts in plasmas from patients with simple factor V deficiency or Factor VIII deficiency. It is suggested that the molecular basis for combined Factor V/VIII deficiency that exhibits simple autosomal recessive inheritance is a deficiency of protein C inhibitor.